Mapping Research Trends, Themes, and Future Directions of Teaching Factory in Vocational Education: A Systematic Literature Review - Sefthy P B Syahailatua; Widihastuti Widihastuti (Integrated Science Education Journal, 2026)
Purpose of the study: Despite the growing number of Teaching Factory studies, a comprehensive synthesis of its research development remains limited. Therefore, this study systematically reviews Teaching Factory research in vocational education published between 2017 and 2026 to identify publication trends, methodological characteristics, major research themes, research gaps, and future research directions. Methodology: This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature was retrieved exclusively from the Scopus database using predefined search terms related to Teaching Factory and vocational education. Of 64 identified records, 20 peer-reviewed journal articles meeting the inclusion criteria were analyzed using descriptive and thematic synthesis. Main Findings: The findings revealed a fluctuating but increasing publication trend, with quantitative studies representing the dominant research approach. Six major research themes were identified: Teaching Factory implementation and evaluation, employability and work readiness, industry collaboration, entrepreneurship and industrial work culture, model development, and digital transformation. Several research gaps were also identified, particularly regarding empirical validation, longitudinal research, industry partnership evaluation, and Digital Teaching Factory development. Novelty/Originality of this study: Unlike previous reviews that examined specific aspects of Teaching Factory, this study provides an integrated evidence-based synthesis of publication trends, methodological characteristics, thematic evolution, research gaps, and future research directions. It also proposes a future research agenda highlighting the shift from implementation-focused studies toward impact-oriented and digitally driven vocational education research.